The Effect of the Marketing Mix on Customer Purchase Decision in the Mobile Telecommunication Industry in Sub-Sahara Africa - Asamoah, Emmanuel Selase (Journal of Applied Business and Economics, 2021)
This study determined the awareness of the marketing strategies of the mobile telecommunication companies; customers’ purchase decision of products and services provided by the mobile telecommunication companies, and finally the influence of customer awareness of marketing strategies on customer purchase decision. The study adopted a quantitative approach with 300 respondents. The study found that customers of the various mobile telecommunication companies had knowledge of the 7Ps marketing strategies of the mobile service providers. Furthermore, respondent’s intentions to patronize the services of their mobile networks were about the same for all customers. The study also found that customer awareness of the pricing strategy (r=.146, p=.011), product/service strategy (r=.120, p=.038), process strategy (r=.153, p=.008), and promotional strategies (r=.129, p=.025) all have significant positive correlation on customer intention to patronize the services of the telecommunication companies. However, customer awareness of the marketing strategy (marketing mix) played no significant role in predicting the decision of the customer to patronize the services of their mobile telecommunication companies.